A transcription factor TaMYB5 modulates leaf rolling in wheat - Zhu, Zhi; Wang, Jingyi; Li, Chaonan; Li, Long; Mao, Xinguo; Hu, Ge; Wang, Jinping; Chang, Jianzhong; Jing, Ruilian (Frontiers in Plant Science, 2022)
Leaf rolling is an important agronomic trait in wheat (Triticum aestivum L.). Moderate leaf rolling keeps leaves upright and maintains the relatively normal photosynthesis of plants under drought stress. However, the molecular mechanism of wheat leaf rolling remains unclear. Here, we identified a candidate gene TaMYB5-3A that regulates leaf rolling by using a genome-wide association study (GWAS) in a panel of 323 wheat accessions. Phenotype analysis indicated that the leaves of tamyb5 mutants were flatter than that of the wild type under drought condition. A nucleotide variation in the TaMYB5-3A coding region resulted in a substitution of Thr to Lys, which corresponds to two alleles SNP-3A-1 and SNP-3A-2. The leaf rolling index (LRI) of the SNP-3A-1 genotype was significantly lower than that of the SNP-3A-2 genotype. In addition, TaMYB5-3A alleles were associated with canopy temperature (CT) in multiple environments. The CT of the SNP-3A-1 genotype was lower than that of the SNP-3A-2 genotype. Gene expression analysis showed that TaMYB5-3A was mainly expressed in leaves and down-regulated by PEG and ABA treatment. TaMYB5 induces TaNRL1 gene expression through the direct binding to the AC cis-acting element of the promoter of the target gene, which was validated by EMSA (electrophoretic mobility shift assay). Our results revealed a crucial molecular mechanism in wheat leaf rolling and provided the theoretical basis and a gene resource for crop breeding.